2016
DOI: 10.1128/cvi.00211-16
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin M for Acute Infection: True or False?

Abstract: Immunoglobulin M (IgM) tests have clear clinical utility but also suffer disproportionately from false-positive results, which in turn can lead to misdiagnoses, inappropriate therapy, and premature closure of a diagnostic workup. Despite numerous reports in the literature, many clinicians and laboratorians remain unaware of this issue. In this brief review, a series of virology case examples is presented. However, a false-positive IgM can occur with any pathogen. Thus, when an accurate diagnosis is essential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 44 publications
10
61
0
1
Order By: Relevance
“…These properties can lead to greater cross-reactivity and a diminished capacity to discriminate true from false binding. 16 Although our data, in agreement with the plethora of historical data, do not raise concern with regard to the sensitivity in detecting IgM antibodies against PGL-I, they do demonstrate that the addition of both the IgG detection and the protein component retain high specificity in detecting leprosy samples.…”
Section: Discussionsupporting
confidence: 87%
“…These properties can lead to greater cross-reactivity and a diminished capacity to discriminate true from false binding. 16 Although our data, in agreement with the plethora of historical data, do not raise concern with regard to the sensitivity in detecting IgM antibodies against PGL-I, they do demonstrate that the addition of both the IgG detection and the protein component retain high specificity in detecting leprosy samples.…”
Section: Discussionsupporting
confidence: 87%
“…[10] The lower diagnostic sensitivity of IgM in repeat syphilis is compatible with results from other infections where reinfections lead directly to increases in IgG without initial increases in IgM. [17] This study represents the most comprehensive evaluation of EIA and LIA IgM testing on serum from individuals with syphilis that we are aware of. We found that both EIA agreed substantially, albeit that the Mikrogen EIA performed in terms of diagnostic sensitivity better than the Euroimmun assay.…”
Section: Discussionsupporting
confidence: 60%
“…21,23,24 Nevertheless, these cases could represent false-positive IgM testing, as has been reported frequently with serological testing for other viruses. 25 Thus far, there is no report of detection of SARS-CoV-2 in amniotic fluid or breast milk, and it is unclear if vertical transmission occurs when pregnant women become infected during the first or second trimester of gestation. 21 Maternal infection can also lead to severe symptoms in the mother, which can result in birth asphyxia or premature birth.…”
Section: Transmissionmentioning
confidence: 99%